EXPLORING THE HERITAGE. AN ATTEMPTED ANALYSIS OF ARMENIAN SURNAMES WITH ARABIC ORIGIN ASSOCIATED WITH CRAFTS, PROFESSIONS, AND OCCUPATIONS (Journal of Oriental Studies, 2024)
Study of etymology of surnames holds considerable significance, as it can give numerous useful insights, revealing layers of the history, culture and lifestyle of a nation. A significant part of Armenian surnames contains a foreign component. This phenomenon reflects centuries of contact and interaction with different nations, with Armenia being subject to cultural, political, and economic influences and the Armenian language incorporating numerous loanwords. This article focuses on Armenian surnames featuring an Arabic etymological foundation, particularly those indicative of trade, profession, or occupation. The incorporation of Arabic etymological elements into Armenian surnames has been either direct (borrowed from Arabic) or indirect (through intermediary languages, namely Turkish and Persian), giving rise to various iterations and variants of surnames and contributing to the complexity of genealogical analysis. In this article, we endeavor to elucidate upon the genealogy of such surnames, in certain instances proposing our own interpretations and hypotheses as potential resolutions to the existing ambiguities. In this endeavor, our aim is to enrich the scholarly discourse by addressing certain gaps in the coverage of the genealogy of Armenian surnames
Keywords: Etymology of Surnames; Armenian Surnames; Arabic Borrowings; Craft; Profession